The Palace of Nestor at Pylos in Western Messenia. Vol II : The Frescoes - Lang, Mabel L. (Princeton Legacy Library, 2015)
Cover -- Contents -- The Painted Plaster -- Catalogue -- Conclusion -- Plate Reference List.